2011
DOI: 10.1016/j.ajpath.2010.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Increased CDK5 Expression in HIV Encephalitis Contributes to Neurodegeneration via Tau Phosphorylation and Is Reversed with Roscovitine

Abstract: Recent treatments with highly active antiretroviral therapy (HAART) regimens have been shown to improve general clinical status in patients with human immunodeficiency virus (HIV) infection; however, the prevalence of cognitive alterations and neurodegeneration has remained the same or has increased. These deficits are more pronounced in the subset of HIV patients with the inflammatory condition known as HIV encephalitis (HIVE). Activation of signaling pathways such as GSK3␤ and CDK5 has been implicated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 94 publications
(107 reference statements)
4
70
0
Order By: Relevance
“…Chronic HIV and simian immunodeficiency virus [SIV] infection also dysregulate the vascular endothelial growth factor [VEGF] [74], RTKs recepteur d'orgine nantais [73], and platelet-derived growth factor [PDGF] signaling [75]. In addition to these signaling pathways, recent studies have shown that CDK5 is hyper-activated [67, 76, 77] in patients with HAND. Therefore, among other pathways through which Tat might lead to neurodegeneration is by aberrant activation of signaling pathways such as CDK5, which is an important pathway for cell survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic HIV and simian immunodeficiency virus [SIV] infection also dysregulate the vascular endothelial growth factor [VEGF] [74], RTKs recepteur d'orgine nantais [73], and platelet-derived growth factor [PDGF] signaling [75]. In addition to these signaling pathways, recent studies have shown that CDK5 is hyper-activated [67, 76, 77] in patients with HAND. Therefore, among other pathways through which Tat might lead to neurodegeneration is by aberrant activation of signaling pathways such as CDK5, which is an important pathway for cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work indicates that CDK5 might also be involved in the mechanisms of neurotoxicity in patients with HAND [67, 76, 77]. For example, a previous gene array study showed that expression levels of CDK5 and related family members are abnormally expressed in patients with HIVE [94].…”
Section: Introductionmentioning
confidence: 99%
“…Total protein homogenates were prepared from flash-frozen postmortem frontal cortex samples as described. 13 HIV-1 p24 was quantified by ELISA (PerkinElmer, Waltham, MA) on homogenate aliquots containing 20 mg of total protein. Real-time PCR analysis of gene expression.…”
mentioning
confidence: 99%
“…Furthermore, dysregulation of Cdk5 activity may play a role not only in AD but also in several other neurodegenerative disorders, including amyotrophic lateral sclerosis, Parkinson disease, Huntington disease and HIV-associated neurocognitive disorders. 7,11,59,60 Thus, our finding that SNO-Cdk5 mediates neuronal injury may be important not only in AD but also in these other neurological diseases. Moreover, this SNO-Cdk5 its kinase activity, (3) as a negative feedback mechanism, SNO-Cdk5 phosphorylates and inhibits NOS1, (4) SNO-Cdk5 hyperactivates the mitochondrial fission protein Drp1 via transnitrosylation, and (5) excessive mitochondrial fission results in bioenergetic failure and synaptic loss in AD (Fig.…”
Section: Methodsmentioning
confidence: 89%
“…[4][5][6] Dysregulation of Cdk5 activity has been implicated in stroke and many neurodegenerative disorders, including Alzheimer disease, amyotrophic lateral sclerosis, Parkinson disease, Huntington disease and HIV-associated neurocognitive disorders. [7][8][9][10][11][12][13] Under these neurodegenerative conditions, neurotoxic stimuli such as oxidative stress, mitochondrial dysfunction, excitotoxicity, amyloid-β (Aβ) exposure, calcium overload, and neuroinflammation trigger the hyperactivation of Cdk5 via the calciumdependent protease calpain, which cleaves the Cdk5 activator p35 (or p39) into p25 (or p29). [14][15][16][17][18] Thus, the accumulation of p25, due to the conversion of p35 to p25 (or p39 to p29), activates various events associated with neurodegeneration.…”
Section: S-nitrosylation Of Cdk5mentioning
confidence: 99%